2018
DOI: 10.1177/0363546518794664
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Mesenchymal Stem Cells Derived From the Cotyloid Fossa Synovium Have Higher Self-renewal and Differentiation Potential Than Those From the Paralabral Synovium in the Hip Joint

Abstract: Synovial cells from the cotyloid fossa synovium of patients with femoroacetabular impingement syndrome are more robust in vitro, suggesting that MSCs from this source may be strongly considered for stem cell therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…Murata et al [52] selected two parts for research: the paralabral synovium and the cotyloid fossa synovium, both of which come from the hip joint of femoroacetabular impingement syndrome patients. The anatomical location of the cotyloid fossa is defined in the lower part of the acetabulum, surrounded by the surface of the acetabular horseshoe-shaped crescent [53].…”
Section: Different Cell Subpopulations Of Sm-mscsmentioning
confidence: 99%
“…Murata et al [52] selected two parts for research: the paralabral synovium and the cotyloid fossa synovium, both of which come from the hip joint of femoroacetabular impingement syndrome patients. The anatomical location of the cotyloid fossa is defined in the lower part of the acetabulum, surrounded by the surface of the acetabular horseshoe-shaped crescent [53].…”
Section: Different Cell Subpopulations Of Sm-mscsmentioning
confidence: 99%
“…One of the other aspects of the definition of MSCs offered by the ISCT is the differentiation potential of the cells into osteocytes, adipocytes, and chondrocytes in vitro. Synovium-derived MSCs have been shown to differentiate into these three cells [6, 49, 50]. Although Alt et al [46] found that fibroblasts exhibited no differentiation potential, other studies have shown that fibroblasts do possess the potential to differentiate into osteocytes, adipocytes, and chondrocytes [45, 47, 51].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have conducted investigations of PBSCs in cartilage repair and regeneration because of the advantages of PBSCs and limitations of chondrogenic progenitor cells from other sources, such as bone marrow (Bain, 2003), synovial membranes (Murata et al, 2018), and adipose tissue (Kuroda et al, 2015). Increasing evidence has shown that PB-MSCs have a similar potential for proliferation and trilineage differentiation as BM-MSCs and might be a promising source of seed cells for cartilage repair (Wang et al, 2016b) since Fernández et al (Fernandez et al, 1997) reported the presence of stromal cells in hG-CSFmobilized PB from patients with breast cancer for the first time in 1997.…”
Section: Discussionmentioning
confidence: 99%